Unique Phenotypes and Functions of Follicular Helper T Cells and Regulatory T Cells in Sjögren’s Syndrome - Saito, Masako (Curr Rheumatol Rev, 2018)
Sjogren’s syndrome (SS) is a T cell-mediated autoimmune disease of the systemic exocrine glands, such as salivary and lacrimal glands. A variety of T-cell subpopulations maintain immune tolerance in the thymus and periphery through complex immune responses including cellular and humoral immunity. The T-cell subpopulations exhibiting abnormal or unique phenotypes and impaired functionality have been reported to play important roles in the cellular mechanisms of autoimmunity in SS patients and animal models of SS. In this review, we focused on follicular helper T cells related to antibody production and regulatory T cells to control immune tolerance in the pathogenesis of SS. The unique roles of these T-cell subpopulations in the process of the onset or development of SS have been demonstrated in this review of recent publications. The clinical application of these T-cell subpopulations will be helpful for the development of new techniques for diagnosis or treatment of SS in the future.